Role of macroeconomic factors predicting financial performance of commercial banks in Nepal (The International Research Journal of Management Science, 2021)
Purpose: This study analyzes the effect of macroeconomic indicators such as domestic products, interest rate, inflation rate, and unemployment rate on the financial performance of commercial banks in Nepal.Design/Methodology: Five top commercial banks based on the financial performance were selected with stratified sampling, with secondary data of ten years. Hausman test was used to examine the endogeneity issue in the predictor variables and the effect of predicators on financial performance were estimated using OLS estimation (random effect model).Findings: The study result revealed significant influence of macroeconomic factors except the unemployment rate for estimating ROE of commercial banks in Nepal while no significant impact was revealed for ROA. Among the significant variables, GDP contributes more in predicting the financial performance of commercial banks in Nepal.Implication: As the study found significant role of macroeconomic variables to estimate ROE, bank administrators, government officials, and investors can focus in such variables, especially in GDP for competitive financial performance. They need to develop products based on macroeconomic variables. Besides, this study finds and tries to mitigate the gap in findings of previous empirical studies.Originality/value: This study contributes to the literature on macroeconomic determinants predicting financial performance of banks, more specifically in finding the gap in determining ROA and ROE within the country specific issue.